2009
DOI: 10.1007/s11661-009-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Stray Grain Formation in Welds of Single-Crystal Ni-Base Superalloy CMSX-4

Abstract: Autogenous welds on the single-crystal (SX) alloy CMSX-4 were prepared over a wide range of welding parameters and processes to investigate the formation and behavior of stray grains (SGs). The quantity and location of SGs in the welds were analyzed by orientation imaging microscopy (OIM). Heat-and fluid-flow modeling was conducted to understand the influence of welding parameters on the local solidification conditions and resultant SG formation tendency.The results indicate that constitutional supercooling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…Although a positive identification of stray grains requires orientation imaging microscopy (IOM), previous studies, such as Anderson et.al. [7], have shown that the darketching grains coincide with strain grains identified via OIM. This is not surprising, because under a given etching condition for optical metallography, cross-sectioned stray grains would expose a crystal plane other than the matrix crystal plane to the etching reagent.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Although a positive identification of stray grains requires orientation imaging microscopy (IOM), previous studies, such as Anderson et.al. [7], have shown that the darketching grains coincide with strain grains identified via OIM. This is not surprising, because under a given etching condition for optical metallography, cross-sectioned stray grains would expose a crystal plane other than the matrix crystal plane to the etching reagent.…”
Section: Resultsmentioning
confidence: 82%
“…Note the microfissure is melted by the pulse marked by the dashed line Fig. 9 The numerical model predicted that the upper left quadrant (that contains points P10, P11, and P20) is the most likely region to form microfissures, where thermal gradient is low to promote stray grain, and thermal stresses are high to enhance crack opening (based on [7]) estimated by the temperature gradient, G. A greater G leads to a smaller volume fraction of equiaxed dendrites, and therefore prevents the formation of the stray grains for a given bead shape [11]. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The COM in Figure 3(b) shows that these grains are randomly orientated. Such randomly orientated grains are often referred to as "stray grains" [16]. SEM-EDS analysis showed the bright inter-columnar phase to be a Ta-Hf-based carbide, the formation of this intercolumnar carbide phase is due to partitioning effects of Ta, Hf and carbon to the liquid phase during solidification [17].…”
Section: Results: Substrate Characterisationmentioning
confidence: 99%
“…Anderson et al [17,18] combined a 3-D heat transfer and fluid flow code for welds and an SX development model to study the influence of processing parameters on the solidification parameters and associated stray grain formation in weld bead. They found that the stray grain content initially increased and then decreased with increasing travel speed, while the increase in laser beam power resulted in an increase in stray grain content.…”
Section: Introductionmentioning
confidence: 99%